Mandates of the State: Canadian Sovereignty, Democracy, and Indigenous Claims. Issue 1 (January 2014) - Rollo, Toby
Abstract : Indigenous peoples encounter restrictions on their modes of reasoning and account-giving within democratic sites of negotiation and deliberation. Political theorists understand these restrictions as forms of exclusion related to what theorist Iris Young has called the 'internal exclusion' of subordinated perspectives and theorist James Bohman has referred to as the 'asymmetrical inclusion' of such perspectives. 'Internal exclusion' refers to ways in which actors are formally accepted into decision-making processes, only to find their perspectives disqualified due to informal but no less pervasive criteria of exclusion. 'Asymmetrical inclusion' refers to the undue burdens placed on marginalized peoples to persuade dominant communities. It is argued in light of these problems that more inclusive institutions as well as the cultivation of an ethos of receptivity will be necessary for genuine inclusion. I argue that this focus on enriching dialogue can mischaracterize the nature of disagreement between Indigenous and non-Indigenous peoples. Disagreement does not only arise between opinions or discourses that can be articulated and judged, but also at a deeper level, between the background assumptions against which practices of articulation and judgment are understood. Territorial state sovereignty, I argue, is a background understanding that can render sites of democratic negotiation inhospitable to Indigenous claims. I conclude that when thinking through Indigenous equality and autonomy, theorists should be attuned to the sites and conditions of dialogue that might serve to reinscribe relations of domination and exclusion.